Nilai Pendidikan Karakter Peduli Sosial Anak Usia Dini Dalam Serial Animasi Adit Sopo Jarwo Karya MD Animation Episode “Cara Jitu Dennis Jadi Pemberani” - Septiana, Carolina; Ernawati, Fetty (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2023)
This study aims to determine the value of social care character education for early childhood in the animated series Adit Sopo Jarwo by MD Animation in the episode "The Right Way to Be Brave Dennis". This type of research is a literature study using descriptive methods. The primary data source for this study was from the animated video series Adit Sopo Jarwo episode "Cara Jitu Dennis Jadi Pemberani", while the secondary data source for this research was from books and journals that could explain the research objectives. The data analysis technique of the data in this study is the content analysis technique. The results of this study are that there are 4 social care character education for early childhood in the animated series Adit Sopo Jarwo in the episode "Cara Jitu Dennis Jadi Pemberani", namely: 1) please help there are 5 scenes which are depicted by scenes of mutual help between characters using exemplary strategies ; 2) empathy, there are 3 scenes which are illustrated by dialogue asking about the situation and participating in feeling what other people feel using exemplary strategies; 3) tolerance, there are 3 scenes that are depicted by living in harmony even though they are of different ethnicities and understand each other's weaknesses and strengths using exemplary and habitual strategies; and 4) collaboration, there are 3 scenes which are described by scenes together solving a problem using habituation and exemplary strategies.